C-reactive protein and angiographic coronary artery disease: independent and additive predictors of risk in subjects with angina - Zebrack, James S; Muhlestein, Joseph B; Horne, Benjamin D; Anderson, Jeffrey L (Journal of the American College of Cardiology, 2002)
The objective of this study was to determine the prognostic value of C-reactive protein (CRP) independent of coronary angiographic findings. High sensitivity CRP, a marker of inflammation, predicts risk of cardiovascular events. However, it is uncertain whether it remains predictive once angiographic findings are considered. A total of 2,554 patients with angina but without acute myocardial infarction (MI) were studied angiographically; 1,848 patients had coronary artery disease (CAD) and 706 patients did not. Coronary artery disease was quantified in five ways and combined for a CAD score. C-reactive protein was measured and patients were followed for up to five years for death or MI. C-reactive protein correlated with the extent of CAD, but correlation coefficients were low (0.02 to 0.08). Of angiographic measures, the CAD score best predicted future events (hazard ratio [HR] = 1.8 [1.2 to 2.6], p = 0.004, for CAD score >4). C-reactive protein ≥1.0 mg/dl was predictive in both patients without CAD (HR = 2.3 [0.9 to 5.5], p = 0.07) and with CAD (HR = 2.1 [1.5 to 3.1], p = 0.0001). Multivariate adjustment resulted in little change in HR. C-reactive protein retained predictive value within each quintile of CAD score. C-reactive protein and CAD independently and additively contributed to the risk prediction: low CRP and lowest CAD score was associated with lowest risk, and high CRP and highest CAD score was associated with the highest risk, with a 10-fold difference between extremes (2.5% vs. 24%). C-reactive protein correlates with extent of CAD, but the degree of correlation is low. Severity/extent of CAD and CRP are independent and additive predictors of risk. Therapy should target CRP-associated risk as well as angiographically evident stenosis.